Interaction between asthma and anxiety: a systematic review of cognitive-behavioural therapies and a qualitative exploration of young people’s experiences. - Pateraki, Eleni (The University of Edinburgh, 2015)
Aims: There is a well-established link between asthma and anxiety, leading to exacerbations for both conditions. National guidelines and policy documents recommend the provision of psychological interventions for this comorbidity, although evidence for their effectiveness is inconclusive. This thesis had two objectives: a) to evaluate cognitive-behavioural therapy (CBT) interventions for reducing anxiety in adults and/or children with asthma, given that CBT has a stronger evidence base for relevant respiratory and mental health conditions, b) to explore the lived experience of the interplay between childhood asthma and anxiety directly from the affected population in order to identify specific thinking and behaviour patterns that may maintain this comorbidity. Method: The first journal article outlined a systematic review. Three major electronic databases and manual searches were used to find relevant published and unpublished research. Trials meeting inclusion criteria, primarily utilising validated anxiety measures and employing both cognitive and behavioural techniques, were evaluated using adapted quality criteria. The second empirical article implemented interpretative phenomenological analysis (IPA) to explore the mechanisms maintaining the interplay between asthma and anxiety as experienced by 11 young people (aged 11-15) living with the comorbidity. Results: Fourteen trials met the inclusion criteria for the systematic review. The reviewed trials showed reasonable preliminary support for the effectiveness of CBT for anxiety in individuals with asthma across the age range. The favourable results were largely maintained long-term. The empirical article revealed three super-ordinate themes: i) ‘the influence of asthma’ by inhibiting valued activities or developmental tasks, triggering catastrophic thinking and leading to a generalisation of asthma coping strategies to managing anxiety; ii) ‘the influence of anxiety’ by affecting appropriate medication use and triggering hyperventilation-induced asthma exacerbations; and iii) ‘the interaction between asthma and anxiety’ by forming an unhelpful positive feedback loop and triggering symptom confusion. Conclusions: The systematic review discussed the moderate overall study quality and called for more methodologically robust research, examining CBT models tailored to this population and utilising clinically representative samples. The empirical article pointed to possible maintaining mechanisms identified, which lend themselves to a cognitive-behavioural framework, potentially including mindfulness-based interventions, and may be used to tailor psychological treatments.
Keywords: asthma; anxiety; CBT; cognitive-behavioural therapy; Interpretative Phenomenological Analysis; IPA; systematic review